Roads to Nowhere : How Corruption in Public investment Hurts Growth. (Economic Issues; Economic Issues ;, 1998)
In some countries, corrupt politicians appear to choose investment projects based on the opportunity for bribes and kickbacks these projectspresent. This paper contends that such corruption increases the numberof capital projects undertaken and trends to enlarge their size andcomplexity. The result is that, paradoxically, some public investmentcan end up reducing a country's growth.